Ketamine increases the expression of GluR1 and GluR2 α-amino-3-hydroxy-5-methy-4-isoxazole propionate receptor subunits in human dopaminergic neurons differentiated from induced pluripotent stem cells. Issue 3 (6th February 2019) - Collo, Ginetta; Cavalleri, Laura; Chiamulera, Cristiano; Merlo Pich, Emilio
Abstract : The mechanisms underlying the prolonged antidepressant effects after a single exposure to ketamine are only partially understood. Converging findings indicate a critical role of structural neuroplasticity, recently also proposed for dopaminergic (DA) neurons known to be involved in a depression core symptom, anhedonia. We recently showed that ketamine induces dendritic outgrowth in human DA neurons differentiated in-vitro from induced pluripotent stem cells of healthy donors, a phenomenon blocked by the α-amino-3-hydroxy-5-methy-4-isoxazole propionate receptor antagonist NBQX. As changes in the expression of AMPA receptor subunits GluR1 and GluR2 were observed in neuroplasticity of rodent DA neurons, we aimed to explore this phenomenon in human DA neurons. Using specific antibodies against GluR1 and GluR2 α-amino-3-hydroxy-5-methy-4-isoxazole propionate receptor subunits, we showed that GluR1 levels were significantly higher in soma than in dendrites, whereas for GluR2, levels were significantly higher in dendrites than in soma. One hour exposure to 1 µM ketamine increased the signal of both subunits in dendrites, but only of GluR2 in soma, at 24, 48, and 72 h. Nonlinear polynomial fitting of dendritic expression indicated that the two curves were significantly different, with stronger and more sustained effects on GluR2 expression. Overall, these data support a role for GluR1 and GluR2 dendritic upregulation in driving structural plasticity in human DA neurons depending on ketamine transient exposure, indicating translationally relevant downstream mechanism possibly involved in antidepressant effects.